2023
DOI: 10.1017/cjn.2023.18
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Landscape of Equitable Access to Advanced Neurotechnologies in Canada

Abstract: ABSTRACT:Geographic, social, political, and economic factors shape access to advanced neurotechnologies, yet little previous research has explored the barriers, enablers, and areas of opportunity for equitable and meaningful access for diverse patient communities across Canada. We applied a mixed-mode approach involving semi-structured interviews and rating scale questions to consult with 24 medical experts who are involved in the care of patients who undergo functional neurosurgery targeting the brain. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Topics discussed under neuroethics in recent times ranged from dealing with "existing sexist and androcentric biases within neuroscientific research" [53] and the ethics of neuroscience [54] to invasive neurotechnologies [55] and that ethics has to be included in neuro-engineering education [56]. Ethics in general has recently been covered in relation to neuro-advancements, for example, in regard to the use of neurotechnologies in education [57], human enhancement [58][59][60], equitable access to neurotechnologies [61], diversity of stakeholders [62], and socially aligned networks [63]. A recent study interviewing DIY neurohackers found the following motivations for DIY neurohacking: "In short, neurohackers might simultaneously seek to manage a physical or psychological condition and to experiment with implants that open doors, pay bills or give them new senses.…”
Section: Neurotechnologies and Neuro/cognitive Enhancements: Disabled...mentioning
confidence: 99%
“…Topics discussed under neuroethics in recent times ranged from dealing with "existing sexist and androcentric biases within neuroscientific research" [53] and the ethics of neuroscience [54] to invasive neurotechnologies [55] and that ethics has to be included in neuro-engineering education [56]. Ethics in general has recently been covered in relation to neuro-advancements, for example, in regard to the use of neurotechnologies in education [57], human enhancement [58][59][60], equitable access to neurotechnologies [61], diversity of stakeholders [62], and socially aligned networks [63]. A recent study interviewing DIY neurohackers found the following motivations for DIY neurohacking: "In short, neurohackers might simultaneously seek to manage a physical or psychological condition and to experiment with implants that open doors, pay bills or give them new senses.…”
Section: Neurotechnologies and Neuro/cognitive Enhancements: Disabled...mentioning
confidence: 99%
“…Digital technologies have the capacity to ameliorate or compensate for existing racial, geographic, and socioeconomic disparities. For instance, appropriately deployed and supported telemedicine can improve the management of chronic disease and access to specialist consultations for people in rural or low-mobility populations [ 9 , 35 ]. Efforts to ameliorate racial bias in the accuracy of wearables such as pulse-oximeter accuracy, for example, require recruiting a diverse population during test and validation research [ 26 ].…”
Section: Imperative For Diverse Research Populationsmentioning
confidence: 99%
“…For example, genomics research with indigenous communities has long been held to pose special risks to individuals and communities alike and requires enhanced protocols for collaboration, cultural competency, transparency, and community capacity building [5]. Neuroscience research has followed suit as perspectives on the brain and mind extend well beyond western concepts [6,7], and equitable access to translational interventions remains unrealized [8][9][10]. Collaborative approaches to research, including participatory action methods toward the cocreation of studies and knowledge sharing have been developed in response.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 With a worsening opioid crisis worldwide, there is an imperative to explore all promising treatments for opioid use disorder (OUD), and with the disproportionate burden among marginalised communities, understanding the ethics of implementation is a critical task to ensure that accessibility and equity, alongside cultural meaningfulness, are at the forefront of discussions. [19][20][21] Here, we examine the current state of the science and ethical considerations of neuromodulation for OUD as a case study. We focus on DBS, rTMS, transcranial direct current stimulation (tDCS) and percutaneous electrical stimulation (BRIDGE) because of evidence of their early applications in Europe and Asia, as well as their growing availability in Canada.…”
Section: Introductionmentioning
confidence: 99%